Influence of Related Party Transaction, CEO Narcissism, and Political Connection to Tax Avoidance on Manufacturing Companies in The Consumer Goods Industry Sector Listed On The Indonesia Stock Exchange For The Period 2017-2019 - Nada Nabilah; Nafis Dwi Kartiko; Ismi Fathia Rachmi (Institute of Computer Science (IOCS), 2022)
This research aims to analyze the effect of related party transaction- receivable, related party transaction-liabilities, CEO narcissism, political connection, profitability, leverage, and company size on tax avoidance on manufacturing company sector consumer goods industry listed on Indonesia Stock Exchange for the period 2017-2019. The data analysis method used is a multiple linear regression analyst using SPSS version 25. The sample selection technique is purposive sampling and obtained a sample of 27 companies. This research shows that related party transaction liabilities and company size have a positive effect and significant on tax avoidance. CEO narcissism, profitability, and leverage have a negative effect on tax avoidance. Related party transaction-receivable and political connection have no positive effect on tax avoidance.